Distributed, immersive and multi-platform molecular visualization for chemistry learning - dos Santos Baglie, Luiz Soares [UNESP] (2017)
This paper presents Dimmol (acronym for Distributed Immersive Multi-platform Molecular visualization), a scientific visualization application based on UnityMol, developed with the Unity game engine, and that uses the Unity Cluster Package to enable distributed and immersive visualization of molecular structures across multiple device of different types, with support to Google VR, molecular trajectory files, and master-host-slave rendering. Its goal is to improve and facilitate the way educators and researchers visualize molecular structures with students and partners. In order to demonstrate a possible use scenario for Dimmol, better understand the contributions of each platform it can be executed in, and gather performance data, three molecular visualizations are loaded on it and distributed to a graphic cluster, a laptop, a tablet, and a smartphone. Other possible uses are also discussed.